Pengelolaan Pembelajaran Tematik Di Sdn Kemasan I No. 64 Surakarta - Utomo, Budi, Dr. Eko Supriyanto, SH., M.Hum (2017)
This study describes how teachers grade I, II, and III SDN Kemasan I Surakarta manage thematic learning from planning, implementation, and assessment. This research used qualitative research with research subjects principals, teachers of class I, II, and III. The data collection technique are by interview, documentation, observation, and questionnaires. Data analysis technique used is interactive analysis model, namely through data collection, data reduction, data presentation and the conclusion. To obtain such data validity, then used triangulation. The results showed that in planning the teacher has not made a competency mapping as it should. On implementation, the learning is dominated by teachers and materials are still fragmentary. Learning has not centered on the theme and learners. The types of assessment used by teachers are a field test, multiple choice and description. Teachers assessed only on the cognitive domain alone while on the affective and psychomotor yet done. Teachers are still obstacles to the plan that is preparing a syllabus of thematic learning. Another obstacle encountered in the implementation of the teacher is still difficulty in creating a student-centered learning and the lack of teaching aids also be a limiting factor in the implementation of thematic learning in SDN Kemasan I Surakarta.